SMA actuator material model with self-sensing and sliding-mode control; experiment and multibody dynamics model. (3rd February 2017) - Lambert, Tyler Ross; Gurley, Austin; Beale, David
Abstract: Shape memory alloys (SMA) can be used to create actuators that are simple, high strength, and inexpensive. These benefits come at the cost of low electrical efficiency, moderate lifetime, and complex mechanical behavior that makes them difficult to design into new applications and products. To improve the integration of SMA actuators—in particular thin SMA wires heated by passing electric current through them—into modern mechanical applications, we have created tools for modeling SMA mechanical and thermal behavior in dynamic systems and under feedback controls. Thermo-electro-mechanical constitutive models are implemented in a multibody dynamics software where they are easily applied to an actuator emplaced in a multibody dynamic system. Mechanical behavior is modeled with 1D constitutive equations. The material state determines the electrical resistivity of the material which drives ohmic heating, while thermal cooling is based on a heat transfer analysis of thin cylinders. These models contain states which are very difficult to measure experimentally (such as crystal phase fraction) and thus provide insight into the material behavior and design that experimental results cannot offer. This thermomechanical model is used in conjunction with sliding mode control—historically difficult to simulate in numerically integrated models—to develop a working ball-on-a-beam setup in which the ball position is controlled via current passed through an SMA wire and with application of an original self-sensing method. The constitutive model is developed in the multibody dynamics software MSC ADAMS and validated through the simulation of the same system.